2019
DOI: 10.1002/er.4406
|View full text |Cite
|
Sign up to set email alerts
|

The energy performance of a single‐screw compressor for natural gas liquefaction process: Effects of the lubricating oil flow rate

Abstract: Summary An experimental test system including the oil circulation system and the gas circuit system has been designed and built to explore the effects of the lubricating oil flow rate on the performance of a single‐screw compressor, used in a portable natural gas liquefaction process. Outlet pressure, outlet volumetric flow rate, volumetric efficiency, and specific power rate are the parameters for evaluation of the energy performance of the single‐screw compressor. The experimental results indicate that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The study also demonstrated that the temperature-dependent dynamic viscosity of oil should be considered for reasonable modelling especially at high circumferential speeds, while the influence of water temperature can be negligible. Researchers always focused on finding the proper flow rate of injected oil or water [111][112][113][114][115], which depended on working conditions and the capacity of screw machines. The consistent findings were that a certain amount of oil or water can effectively improve the performance of screw machines, but further increase in the injection flow rate had little or even bad effect, and thus the optimal flow rate or injection orifice size existed.…”
Section: Liquid Injection Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The study also demonstrated that the temperature-dependent dynamic viscosity of oil should be considered for reasonable modelling especially at high circumferential speeds, while the influence of water temperature can be negligible. Researchers always focused on finding the proper flow rate of injected oil or water [111][112][113][114][115], which depended on working conditions and the capacity of screw machines. The consistent findings were that a certain amount of oil or water can effectively improve the performance of screw machines, but further increase in the injection flow rate had little or even bad effect, and thus the optimal flow rate or injection orifice size existed.…”
Section: Liquid Injection Technologymentioning
confidence: 99%
“…Yang et al [164] developed a MVR system employing a water-injected SSC and found that water injection can lead to a significant increase in evaporation capacity, pressure ratio, and specific moisture extraction rate. Some scholars investigated the performance of screw machines used in the process of natural gas delivery and use, such as the TSE for pressure energy recovery in the pressure reduction process [165][166][167], the SSC for natural gas liquefaction process [112,168], and the TSC for coal seam gas compression [169]. Most of these screw machines were of the oilinjected type, while Diao et al [165] introduced an oil-free TSE to recover pressure energy at a city gas station for the first time and its actual isentropic efficiency was about 70% at all tested operating conditions.…”
Section: Other Popular Applicationsmentioning
confidence: 99%
“…Lu et al manufactured a mini SSC with a refrigerating capacity of 2.02 kW to cool CPUs [8]. Li et al simulated a new natural gas liquefaction process, designed and tested an SSC for the process, and conducted performance testing to investigate the optimum oil-gas ratio and motor speed [9,10]. Yang et al investigated the SSC performance in a mechanical vapor recompression system with different amounts of injected water [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the exergy theory, Wu et al studied shaft power wastage, classifying it into four components: irreversible heat transfer, adiabatic throttling, mixing of two flows, and heat dissipated to the environment, indicating that the exergy loss decreased with increasing rotating speed [38]. Li et al analyzed the thermal process of an oil-flooded SSC using natural gas liquefaction and tested its main energy efficiency indices [9,10]. It can be seen that the published studies related to the thermodynamic performance of SSCs are mostly focused on the refrigeration SSC and the oil-flooded SSC.…”
Section: Introductionmentioning
confidence: 99%